Market Analysis and Business Operations of Online Food Delivery Around STIE Ganesha - Saefullah, Aep; Siregar, Fuad Gagarin; Noor, M. Arief; Salima, Rianti; Rosliana, Rosliana (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the market dynamics, operational challenges, and competitive strategies of SMEs in the online food delivery sector around STIE Ganesha, with a focus on identifying performance drivers and actionable solutions for business optimization. Methodology/approach: A qualitative descriptive approach was adopted, involving semi-structured interviews with 20 SME owners using GoFood, GrabFood, and ShopeeFood. Data were collected from December 2024 to February 2025 and analyzed thematically to map operational patterns and market behaviors. Results/findings: Key determinants of customer retention included taste quality (highlighted by 85% of respondents), service speed (70%), and promotional effectiveness (65%). SMEs leverage product differentiation (e.g., hyperlocalized menus) and platform partnerships to sustain their market share. However, challenges persist, such as platform instability (reported by 60% of businesses) and insufficient digital literacy for advanced marketing tactics. Conclusions: The study underscores that SMEs’ competitiveness in campus-centric markets hinges on balancing micromarket responsiveness (e.g., adapting to seasonal demand) with operational agility. The strategic integration of digital tools and collaborative logistics, rather than reliance on third-party platforms alone, has emerged as critical for scalability. Limitations: The findings are context-bound to SMEs near STIE Ganesha and major delivery platforms. Future studies should explore rural and non-campus ecosystems to validate the universality of the proposed strategies. Contribution: Theoretical: Expands the Resource Orchestration Framework by contextualizing SME strategies in hyper-localized digital economies. Introduces a micro market analysis model linking campus-specific demand cycles to operational decision-making.Practical: Provides actionable toolkits, including a Dynamic Pricing Matrix for demand fluctuations and a Partnership Optimization Framework for platform collaboration. Methodology/approach: The study was conducted from December 2024 to February 2025, employing a descriptive qualitative approach. Data were collected through semi-structured interviews with 20 business owners using platforms such as GoFood, GrabFood, and ShopeeFood. Results/findings: The taste quality, fast service, and effective promotions are crucial for attracting and retaining customers. Despite high competition, SMEs have maintained their market positions through product differentiation, flavor innovation, and promotional packages. Although online delivery platforms offer substantial support, respondents highlighted the need for improved platform stability and more consistent promotional efforts. They also expressed the importance of training in digital marketing and operational management to enhance competitiveness. Limitations: This study is limited to SMEs operating around STIE Ganesha and on major online platforms. Broader generalizations require similar studies in different regions with varying business models. The research contributes to the fields of entrepreneurship and business management by providing insights for policymakers, platform providers, and business associations. Contribution: These insights focus on supporting SMEs through training, platform partnerships, and strategic collaborations. The research focused on operational processes, customer service, marketing strategies, and platform support. Novelty : The exploration of how platform partnerships, operational innovation, and digital marketing strategies influence the performance of SMEs in the online food delivery market, a topic that has not been extensively explored in prior research.